Kesalahan Sintaksis dalam Website Berita CNN Periode Agustus 2025 - Ahkmad Maulana Marzuki; Andika Kurniawan Luthfi; Nadif Abinaya Yulkham; Ilham Kusuma Aji; Asep Purwo Yudi Utomo; Deby Luriawati Naryatmojo; Luthfa Nugraheni (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This research is driven by the urgency of maintaining the quality of the Indonesian language in the realm of online journalism, particularly on major media platforms such as CNN Indonesia. Online media plays a central role as the primary source of information, but the speed of publication often encounters linguistic errors that have the potential to damage credibility and lead to misinterpretation among readers. The focus of the study on syntactic errors is crucial because errors in sentence structure, diction, and conjunctions directly affect the meaning and effectiveness of communication. This study aims to analyze and describe the forms of syntactic errors (including sentence pattern errors, non-standard diction, and conjunction redundancy) and offer recommendations for improvement based on standard Indonesian language rules. The method used is a qualitative descriptive approach with a syntactic approach. Data in the form of linguistic units at the phrase, clause, and sentence levels from all CNN Indonesia news texts for the period of August 2025, collected using the Listen and Note Technique. The findings are anticipated to show a dominance of sentence ineffectiveness, incorrect use of conjunctions, and temporally illogical diction errors. This research is expected to contribute as a practical guide for editors and news writers to improve the quality of editing, while also supporting literacy efforts and the use of good and correct Indonesian in the digital public space.